Scoping Review: Efektivitas Chest X-Ray Brixia Score untuk Menilai Derajat Keparahan COVID-19 - Natassja Salsabilla; Yani Triyani; Dyana Eka Hadiati (Bandung Conference Series: Medical Science, 2022)
Abstract. The use of chest x-rays in Covid-19 pandemic has become an alternative radiological examination that is extensively carried out, although it is less sensitive, but is widely available and its use is mobile to detect lung abnormalities in Covid-19 patients using the brixia score assessment. The purpose of this study was to determine the effectiveness of chest x-rays using the brixia score to assess the severity of Covid-19. This research was taken by scoping review method with a sample of international scientific articles that meet the eligibility criteria. The databases used in this study are Spingerlink, Sciencedirect, Pubmed, Google scholar, and Proquest with the number of articles obtained as many as 833 articles. The results of the screening of articles that met the inclusion criteria were 275 articles and there were three articles that met the eligibility criteria. The results of the three reviewed articles, one article compared the use of chest x-ray and CT in detecting lesions of Covid-19 patients with the result that chest x-ray had low sensitivity. Two articles compared the brixia score in patients who died and discharged with higher outcomes in patients who died. The conclusion of this study shows that the use of chest x-rays is not effective for detecting early-stage abnormalities and the brixia score is effective for assessing the severity of Covid-19 patients. Abstrak. Penggunaan Chest x-ray di era pandemi Covid-19 menjadi pemeriksaan radiologis alternatif yang banyak dilakukan walaupun kurang sensitif, tetapi tersedia luas dan penggunaannya mobile untuk mendeteksi kelainan paru pada pasien Covid-19 menggunakan penilaian brixia score. Tujuan penelitian ini adalah untuk mengetahui efektivitas chest x-ray menggunakan penilaian brixia score untuk menilai keparahan Covid-19. Penelitian ini diambil dengan metode scoping review dengan sampel artikel ilmiah internasional yang memenuhi kriteria kelayakan (eligible). Database yang digunakan pada penelitian ini adalah Spingerlink, Sciencedirect, Pubmed, Google scholar, dan Proquest dengan jumlah artikel yang didapatkan sebanyak 833 artikel. Hasil skrining artikel yang sesuai dengan kriteria inklusi sebanyak 275 artikel dan artikel yang memenuhi kelayakan terdapat tiga artikel. Hasil dari tiga artikel yang telah di-review, satu artikel membandingkan penggunaan chest x-ray dan CT dalam mendeteksi lesi pasien Covid-19 dengan hasil adalah pemeriksaan chest x-ray mempunyai sensitivitas yang rendah. Dua artikel membandingkan nilai brixia score pada pasien meninggal dan dipulangkan dengan hasil lebih tinggi pada pasien meninggal yaitu 12 poin. Kesimpulan penelitian ini menunjukkan penggunan chest x-ray tidak efektif untuk mendeteksi kelainan tahap awal dan brixia score efektif untuk menilai derajat keparahan pasien Covid-19.